Pharmacokinetic and pharmacodynamic profile of dronedarone, a new antiarrhythmic agent for the treatment of atrial fibrillation. (December 2014) - Rosa, Gian Marco; Bianco, Daniele; Parodi, Antonello; Valbusa, Alberto; Zawaideh, Camilla; Bizzarri, Nicolò; Ferrero, Simone; Brunelli, Claudio
<x xml:space="preserve">Abstract</x> Introduction: Atrial fibrillation (AF) is the most common arrhythmia and is associated with increased morbidity and mortality. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Dronedarone&logicalOpe1=OR&field2=articletitle&text2=Dronedarone&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Dronedarone is a recent antiarrhythmic drug that has been developed for treatment of AF, with electrophysiological properties similar to amiodarone but with a lower incidence of side effects. Areas covered: This review evaluates the efficacy, safety, tolerability and side effects of dronedarone in the treatment of AF. In particular, the review includes studies comparing: dronedarone and placebo (ANDROMEDA, ATHENA, DAFNE, ERATO, EURIDIS/ADONIS, HESTIA, PALLAS trials), dronedarone and amiodarone (DIONYSOS trial), ranolazine and dronedarone given alone and in combination (HARMONY trial). Expert opinion: Dronedarone is an interesting antiarrhythmic agent in well-selected groups of patients. It also has several other pleiotropic effects that may potentially be beneficial in clinical practice, such as the reduction of the risk of stroke and acute coronary syndromes. In addition, combination therapies such as those with dronedarone and ranolazine, currently being investigated in the HARMONY trial, may provide another interesting approach to increase the antiarrhythmic efficacy and further reduce the incidence of side effects. A better understanding of the mechanisms underlying dronedarone's pleiotropic actions is expected to facilitate the selection of patients benefiting from dronedarone, as well as the development of novel antiarrhythmic drugs for AF.